Wind turbine impact on near-ground air temperature. (August 2018) - Moravec, David; Barták, Vojtěch; Puš, Vladimír; Wild, Jan
Abstract: Several aspects of wind farms' environmental impacts have been thoroughly studied. Their effect on surface temperature, however, has not been sufficiently explored. We analysed variations in land surface temperature observed over 5 months on a large wind farm (42 000 kW maximum output). To describe the near-surface microclimate variability, we measured air temperature at 15 cm above ground using 14 autonomous microclimatic stations arranged in the vicinity of 4 turbines. The observation covered various weather conditions from summer to winter. In contrast to some other recent studies, we confirmed no clear long-term, stable effect of wind turbines on near-ground temperatures. The only effect we found was a daytime warming effect at one of the four turbines. Our results suggest that in mountainous conditions the effect of turbulence caused by wind turbines can be overridden by natural wind turbulence. Highlights: No stable effect from wind farm on near-ground air temperature was observed. Rare daytime warming effect observed. Local environment could have similar or greater effect than does wind farm.